Effects of irradiation of spray-dried blood meal and animal plasma on nursery pig growth performance - B W James; M J Webster; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2000)
Two trials were conducted to determine the effects of irradiation of spray-dried blood meal and animal plasma on nursery pig growth performance. In Exp. 1, irradiation of spray-dried blood meal resulted in improved ADG and F/G and tended to increase ADFI for the 14 d experiment. The majority of the increase in growth performance occurred during the first week of the trial. In Exp. 2, ADG and ADFI were increased from d 0 to 10 for pigs fed irradiated spray-dried animal plasma compared to pigs fed regular spray-dried animal plasma. In addition, we observed differences in growth performance between different sources of spray-dried plasma used in this experiment.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Nursery pig; Irradiation; Blood meal; Animal plasma